2021
DOI: 10.1186/s12864-021-08131-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiomics study of a heterotardigrade, Echinisicus testudo, suggests the possibility of convergent evolution of abundant heat-soluble proteins in Tardigrada

Abstract: Background Many limno-terrestrial tardigrades can enter an ametabolic state, known as anhydrobiosis, upon desiccation, in which the animals can withstand extreme environments. Through genomics studies, molecular components of anhydrobiosis are beginning to be elucidated, such as the expansion of oxidative stress response genes, loss of stress signaling pathways, and gain of tardigrade-specific heat-soluble protein families designated CAHS and SAHS. However, to date, studies have predominantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 85 publications
0
37
0
Order By: Relevance
“…The targeting of glutathione transferase ( gst ) had no effects on the motilities of injected animals at any time following rehydration. GSTs have been seen to exist in high copy number in several tardigrade species 25 , 71 , implying that P. spatialis may also have a high copy number of these genes. If this is the case, the knockdown of a single putative gene of gst might not be sufficient to perturb anhydrobiosis in this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The targeting of glutathione transferase ( gst ) had no effects on the motilities of injected animals at any time following rehydration. GSTs have been seen to exist in high copy number in several tardigrade species 25 , 71 , implying that P. spatialis may also have a high copy number of these genes. If this is the case, the knockdown of a single putative gene of gst might not be sufficient to perturb anhydrobiosis in this species.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting superoxide dismutase ( sod ) via RNAi did not negatively affect the motility percentages of injected animals at any time of rehydration. Comparing the gene repertoire of different tardigrade species, the duplication of sod genes was observed as a common characteristic of anhydrobiotic tardigrades 25 , 71 . Since P. spatialis is a good anhydrobiont 10 , 48 , it is possible that its sod genes are duplicated as well, and therefore, the targeting of a single sod gene might not be enough to affect the motilities of injected tardigrades, even though the sod genes could play a useful role during desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…These animals might possess another class of stress-dependent filament-forming proteins. Recently, a new heat-soluble protein family termed EtAHS was identified in E. testudo [20]. This protein family or other new ones are likely good candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Through a search for LEA-like heat-soluble proteins that remain soluble even after boiling in tardigrades, we previously identified cytoplasmic-abundant heat-soluble (CAHS) proteins from one of the toughest tardigrade species, Ramazzottius varieornatus [15]. CAHS proteins exhibited almost no similarity with non-tardigrade proteins, and later genome and transcriptome analyses suggested that CAHS proteins are present only in eutardigrades, one of the major classes of the phylum Tardigrada [11,16,17,18,19,20]. Despite the absence of sequence similarity between CAHS proteins and LEA proteins, they share similar biochemical properties, e.g., high-hydrophilicity supporting heat-solubility and structural transition from the disordered state in hydration to a helix under desolvating or dehydrated conditions [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…The importance of antioxidant pathways has been emphasized in molecular [ 106 , 107 , 108 ] and omics analysis on anhydrobiosis [ 73 , 99 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 ]. The expression of superoxide dismutase (SOD), glutathione-S transferase (GST), and catalase is induced during desiccation in the tardigrade Hypsibius exemplaris (Gąsiorek, Stec, Morek and Michalczyk, 2018).…”
Section: Conserved Cellular Maintenance and Repair Pathways Contribut...mentioning
confidence: 99%